2019
DOI: 10.31557/apjcp.2019.20.12.3703
|View full text |Cite
|
Sign up to set email alerts
|

Call for Systematic Population-Based Cervical Cancer Screening: Findings from Community-Based Screening Camps in Tamil Nadu, India

Abstract: India accounts for one-quarter of the worldwide burden of cervical cancer (Ferlay et al., 2012; Institute for health metrics and evaluation , 2011) and 17% of all cancer deaths among women aged between 30 and 69 years. Cervical cancer is the second most common malignancy among women in India (Bruni et al., 2017). It is estimated that cervical cancer will occur in approximately 1 in 53 Indian women during their lifetime compared with 1 in 100 women in developed world (Institute for health metrics and evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Factors associated with cervical cancer screening positive are different among Asian countries; older age, lower educational level, lower socioeconomic status, higher parity in Bangladesh [ 17 ]; coitarche, years of sexual activity, low BMI, multiple partner in Thailand [ 38 ]; older age (> 40 years old), post-menopause, and smoking in rural China [ 39 ]; and younger age (< 30 years old), early marriage (18–<21 years old), and early birth age in India [ 40 ]. A systematic study including 90 papers reported that factors associated with breast cancers in Asia are age, early menarche, late menopause, nulliparity, positive family history, excessive fat consumption, alcohol, and smoking [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with cervical cancer screening positive are different among Asian countries; older age, lower educational level, lower socioeconomic status, higher parity in Bangladesh [ 17 ]; coitarche, years of sexual activity, low BMI, multiple partner in Thailand [ 38 ]; older age (> 40 years old), post-menopause, and smoking in rural China [ 39 ]; and younger age (< 30 years old), early marriage (18–<21 years old), and early birth age in India [ 40 ]. A systematic study including 90 papers reported that factors associated with breast cancers in Asia are age, early menarche, late menopause, nulliparity, positive family history, excessive fat consumption, alcohol, and smoking [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar disadvantage occurs during camp-based screening. 11 Opportunistic screening at PHC served as an alternative to camp-based screening and circumvented the underrepresentation of the working population. Oral examination and identification of premalignant lesions by screening at the primary health centre gave an opportunity for providing de-addiction and counseling.…”
Section: Introductionmentioning
confidence: 99%